Novel bionics developments in gastroenterology: fecobionics assessment of lower GI tract function. (29th June 2021) - Kassab, G S; Gregersen, H; Sun, D; Huang, Z
Abstract: Biomechatronics (bionics) is an applied science that is interdisciplinary between biology and engineering (mechanical, electrical and electronics engineering). Biomechatronics covers a wide area and is probably best known in development of prosthetic limbs, vision aids, robotics and neuroscience. Although the gastrointestinal tract is difficult to study, it is particularly suited for a bionics approach as demonstrated by recent developments. Ingestible capsules that travel the tract and record physiological variables have been used in the clinic. Other examples include sacral nerve stimulators that seek to restore normal anorectal function. Recently, we developed a simulated stool termed fecobionics. It has the shape of normal stool and records a variety of parameters including pressures, bending (anorectal angle) and shape changes during colonic transit and defecation, i.e. it integrates several current tests. Fecobionics has been used to study defecation patterns in large animals as well as in humans (normal subjects and patient groups including patients with symptoms of obstructed defecation and fecal incontinence). Recently, it was applied in a canine colon model where it revealed patterns consistent with shallow waves originating from slow waves generated by the interstitial cells of Cajal. Furthermore, novel analysis such as the rear-front pressure (preload–afterload) diagram and quantification of defecation indices have been developed that enable mechanistic insight. This paper reviews the fecobionics technology and outlines perspectives for future applications.